Family, slavery, and love in the early American republic the essays of Jan Ellen Lewis - Lewis, Jan Ellen 1949-2018 (The Omohundro Institute of Early American History and Culture, 2021)
"One of the finest historians of her generation, Jan Ellen Lewis transformed our understanding of the early U.S. Republic. Her groundbreaking essays defined the emerging fields of gender and emotions history and reframed traditional understandings of the founding fathers and the U.S. Constitution. This book collects thirteen of Lewis's most important essays. Distinguished scholars shed light on the historical and historiographical contexts in which Lewis and her peers researched, wrote, and argued. But the real star of this volume is Lewis herself: confident, unconventional, erudite, and deeply imaginative"--
Keywords: Lewis, Jan Ellen -- 1949-2018; Sozialgeschichte 1787-1866; USA; Lewis, Jan / 1949-2018; United States / History / 1783-1865; United States / Politics and government / 1783-1865; United States / Social life and customs / 1783-1865; Manners and customs; Politics and government; United States; 1783-1865; Essays; History; Aufsatzsammlung